PENGARUH KARAKTERISTIK PEKERJAAN, BUDAYA ORGANISASI, DAN KEPUASAN KERJA PADA KOMITMEN ORGANISASIONAL - S Martono; Gatot Satrio Dirgantoro; Desti Ranihusna; Vini Wiratno P. (Faculty of Economics and Business Diponegoro University, 2018)
The aim of this paper is to investigate the effect of job characteristic, organizational culture, and job satisfaction on organizational commitment. The study population consisted all employees of PD Citra Mandiri Jawa Tengah. The number of samples used in this paper are 83 employees which using saturated samples. Data were collected by quesionere. The analysis model is multiple regression using programme SPSS 16. This paper shows that the high of job characteristic will increase commitment was found. While, the strong of organizational culture will increase organizational commitment were correlated, and the high of job satisfaction will increase organizational commitment. Suggestion for this research are company could make training and development programme, creating a non monotonous atmosphere like meeting outdoor, future research can look for other variabels that effect on organizational commitment with another object and add number of respondents that will help in generalizing the findings of the study.